So we are trying to get the “y” alone, so to undo the division by -8, we will multiply both sides by -8, then simplify.
(-8) y/(-8) = (-8) 1/16
y = -8/16
and simplified:
y = -1/2
9, 2, -5... so is going down by 7 each time, meaning the "common difference" is -7.
Answer:
1/2 pi
Step-by-step explanation:
This is 1/4 of a circle
Find the circumference and multiply by 1/4
1/4 C
1/4 ( 2*pi*r) where r is the radius
The radius is 1
1/2 pi*1
1/2 pi
Answer:
6
Step-by-step explanation:
[x-2]=[4.7-2]=[2.7]=2
f(4.7)=3*2=6
For this case we have to rewrite the given expression algebraically:
the cube of a, is represented as: ![a ^ 3](https://tex.z-dn.net/?f=a%20%5E%203)
the square of b, is represented as:![b ^ 2](https://tex.z-dn.net/?f=b%20%5E%202)
Thus, the product of both expressions is:
![(a ^ 3 * b ^ 2)](https://tex.z-dn.net/?f=%28a%20%5E%203%20%2A%20b%20%5E%202%29)
And twice the product is represented as:
![2 (a ^ 3 * b ^ 2)](https://tex.z-dn.net/?f=2%20%28a%20%5E%203%20%2A%20b%20%5E%202%29)
Answer:
![2 (a ^ 3 * b ^ 2)](https://tex.z-dn.net/?f=2%20%28a%20%5E%203%20%2A%20b%20%5E%202%29)